1999
DOI: 10.1021/jm9806998
|View full text |Cite
|
Sign up to set email alerts
|

New 4-Point Pharmacophore Method for Molecular Similarity and Diversity Applications:  Overview of the Method and Applications, Including a Novel Approach to the Design of Combinatorial Libraries Containing Privileged Substructures

Abstract: A new 4-point pharmacophore method for molecular similarity and diversity that rapidly calculates all potential pharmacophores/pharmacophoric shapes for a molecule or a protein site is described. The method, an extension to the ChemDiverse/Chem-X software (Oxford Molecular, Oxford, England), has also been customized to enable a new internally referenced measure of pharmacophore diversity. The "privileged" substructure concept for the design of high-affinity ligands is presented, and an example of this new meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
357
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(361 citation statements)
references
References 15 publications
2
357
0
2
Order By: Relevance
“…Representative state-of-the-art fingerprint designs include hashed connectivity pathways, 5 structural dictionary-based designs, 6 layered-atom environments, 7 and pharmacophore-type fingerprints. 8 Similarities between database and active reference molecules are quantitatively determined by calculating the pairwise overlap of their fingerprint representations. For this purpose, a variety of similarity metrics have been introduced, the most prominent being the Tanimoto coefficient (Tc).…”
Section: Introductionmentioning
confidence: 99%
“…Representative state-of-the-art fingerprint designs include hashed connectivity pathways, 5 structural dictionary-based designs, 6 layered-atom environments, 7 and pharmacophore-type fingerprints. 8 Similarities between database and active reference molecules are quantitatively determined by calculating the pairwise overlap of their fingerprint representations. For this purpose, a variety of similarity metrics have been introduced, the most prominent being the Tanimoto coefficient (Tc).…”
Section: Introductionmentioning
confidence: 99%
“…The shape of a molecule is often a key factor in determining whether a molecule will be bioactive, and many types of 3D representation have thus been reported in the similarity literature [7]. Examples include fingerprints that encode interatomic distance or angular information [100,101], and descriptions of molecular shape [102,103] and of the distribution of electrostatic charge around a molecule [104,105]. However, these all need to take account of the fact that most molecules are flexible, i.e., they can adopt several or many different 3D shapes (called conformations) (where as a molecule has only a single 2D topology).…”
Section: Resultsmentioning
confidence: 99%
“…In this way, targeted libraries can be designed and higher discovery efficiency may be achieved. Subsequent libraries may be used to fill in gaps in the information derived from the first generation results and to probe more finely the most promising portions of chemical space [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…MCSS has been applied previously to guide the design of much smaller libraries targeted to picornavirus [23]. Other groups have shown that pharmacophore approaches incorporating active site interaction information derived from protein structures improve combinatorial library design [24][25][26][27][28]. Indeed, MCSS molecular probe maps can be used to derive active site pharmacophore models [29].…”
Section: Introductionmentioning
confidence: 99%